Analysis of nonlinear dynamic characteristic of a planetary gear system considering tooth surface friction. (November 2021) - Wang, Jingyue; Liu, Ning; Wang, Haotian; E, Jiaqiang
Based on the lumped mass method, a torsional vibration model of the planetary gear system is established considering the nonlinear factors such as friction, time-varying meshing stiffness, backlash, and comprehensive error. The Runge–Kutta numerical method is used to analyze the motion characteristics of the system with various parameters and the influence of tooth friction on the bifurcation and chaos characteristics of the system. The numerical simulation results show that the system has rich bifurcation behavior with the excitation frequency, damping ratio, comprehensive error amplitude, load and backlash, and experiences multiple periodic motion and chaotic motion. Tooth friction makes the bifurcation behavior of the system fuzzy in the high frequency and heavy load areas, makes the chaos of the system restrained in the low-damping ratio and light load areas, advances the bifurcation point of the system in the small comprehensive error amplitude area, and makes the period window of the chaos area larger in the large-backlash area, which makes the bifurcation behavior of the system more complex.